Land conversions not climate effects are the dominant indirect consequence of sun-driven CO2 capture, conversion, and sequestration - Moritz Adam; Thomas Kleinen; Matthias M May; Kira Rehfeld (Environmental Research Letters)
Removing carbon dioxide (CO _2 ) from the atmosphere is required for mitigating climate change. Large-scale direct air capture combined with injecting CO _2 into geological formations could retain carbon long-term, but demands a substantial amount of energy, pipeline infrastructure, and suitable sites for gaseous storage. Here, we study Earth system impacts of modular, s un-powered process chains, which combine d irect a ir c apture with (electro)chemical c onversion of the captured CO _2 into liquid or solid sink products and subsequent product s torage (sDACCCS). Drawing on a novel explicit representation of CO _2 removal in a state-of-the-art Earth system model, we find that these process chains can be renewably powered and have minimal implications for the climate and carbon cycle. However, to stabilize the planetary temperature two degrees above pre-industrial levels, CO _2 capturing, conversion, and associated energy harvest demand up to 0.46% of the global land area in a high-efficiency scenario. This global land footprint increases to 2.82% when assuming present-day technology and pushing to the bounds of removal. Mitigating historical emission burdens within individual countries in this high-removal scenario requires converting an area equivalent to 40% of the European Union’s agricultural land. Scenarios assuming successful technological development could halve this environmental burden, but it is uncertain to what degree they could materialize. Therefore, ambitious decarbonization is vital to reduce the risk of land use conflicts if efficiencies remain lower than expected.